(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To find out the Prevalence of Congenital Upper Limb Anomalies by its distribution according to Type, Gender, Family history & Cousin marriages in one calendar year. Study Design: cross sectional study. Place and Duration of study: Department of Orthopaedics Medical Teaching Institute Dera Ismail Khan, Pakistan from January 1, 2022 to December 31, 2022. Materials & Methods: Infants (from birth to one year age) of both genders having congenital anomalies of upper extremities were included in this study. Infants with cerebral palsy, birth palsy and birth trauma were excluded. Swanson’s classification was used for classification and types of congenital upper limb anomalies. All cases were analyzed for the type of CULA, gender, family history and parents as first-degree relatives i.e., cousin marriages. Categorical variables were measured as count and percentages while numeric variable was measured as mean and standard deviation, with 5% margin of error and 95% confidence interval, p-value < 0.05 was set as significant. Results: The overall prevalence of congenital upper extremity anomalies was 142(0.26%), which is similar to International ratios. Polydactyly was most common (51 cases) followed by syndactyly (39 cases) and radial club hands (17 cases). The ratio among boys and girls was 52% and 48% respectively. Forty (28%) patients had a positive family history for CULA as compared to 102 (72%) patients, with p-value <0.05 which was significant. One hundred and twelve (79%) patients had their parents as first degree relative i.e., cousin marriages as compared to 30 (21%) patients with no history of cousin marriages, with p-value <0.05 which was significant. Conclusions: In our study it was found that Polydactyly is the commonest congenital upper limb anomaly. There was increased incidence of CULA in Cousin marriages & patients with positive family history for CULA. Increased incidence of CULA was found in boys as compared to girls.